Impact of Angle malocclusions on oral health related quality of life in adolescents - Akturk Ezgi Sunal; Yavuz Fatma Nur; Unsal Humeyra; Seker Elif Dilara (Sciendo, 2024)
To investigate the impact of Angle Class I, Class II, and Class III malocclusions on oral health-related quality of life (OHRQOL) in children aged 11 to 14 years.